2003
DOI: 10.1002/uog.56
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester diagnosis and management of pregnancies implanted into the lower uterine segment Cesarean section scar

Abstract: Objective To describe first-trimester ultrasound diagnosis and management of pregnancies implanted into uterine Cesarean section scars. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
528
4
19

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(561 citation statements)
references
References 21 publications
10
528
4
19
Order By: Relevance
“…With the increasing rate of caesarean section, there is a substantial increase in this condition with better understanding of this disease. The incidence of CS ectopic pregnancy varies from 1:1800 to 2216 pregnancies with rate of 0.15 % in women with previous caesarean section and 6.1 % of all ectopic pregnancies [2,3]. In 2012, Shen et al [4], in their series of 45 patients with CS ectopic pregnancies, in which 42 women (93.3 %) had undergone only one caesarean section, concluded that multiple caesarean sections may not increase the risk of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing rate of caesarean section, there is a substantial increase in this condition with better understanding of this disease. The incidence of CS ectopic pregnancy varies from 1:1800 to 2216 pregnancies with rate of 0.15 % in women with previous caesarean section and 6.1 % of all ectopic pregnancies [2,3]. In 2012, Shen et al [4], in their series of 45 patients with CS ectopic pregnancies, in which 42 women (93.3 %) had undergone only one caesarean section, concluded that multiple caesarean sections may not increase the risk of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…CS scar endometriosis (2 cases) is very rare; however, it could be associated with uterine adenomyosis and can be Ectopic pregnancy or complicated ectopic pregnancy of the CS scar (4 cases) can be seen as a cystic lesion representing the gestational sac with or without a fetal node inside and could represent a medical emergency [10][11][12][13][14][15].…”
Section: Cervical Nabothian Cysts (Fig 6)mentioning
confidence: 99%
“…We have already learned that, similar to other non‐tubal ectopics, 40–50% of these pregnancies fail during the first trimester, but a significant proportion has a potential to progress further 3 .…”
mentioning
confidence: 96%
“…These defects typically communicate widely within the cervical canal, creating a characteristic “niche” in which pregnancy may implant 1 , 2 . Despite a relatively large number of women with deficient Caesarean scars in the population, implantation of pregnancy in this defect is relatively rare 3 . 4 .…”
mentioning
confidence: 99%